Pyrococcus furiosus Argonaute coupled PCR assay for accurate discrimination between the MS-H vaccine strain and clinical isolates of Mycoplasma synoviae - Yanli Zhao; Yinling Wang; Ge Song; Houqiang Luo; Liyan Dong; Qingsong Han; Mengling Yang; Jing Pan; Hongxia Jiang (PLoS ONE, 2026)
Mycoplasma synoviae (MS) is a significant avian pathogen responsible for arthritis, tenosynovitis, airsacculitis, and abnormal eggshell apex syndrome in chickens, posing a substantial threat to the poultry industry. While the attenuated MS-H vaccine has proven effective and is widely implemented in poultry flocks. However, distinguishing the MS-H vaccine strain from wild-type strains remains a persistent challenge. Recently, Pyrococcus furiosus Argonaute (PfAgo) nucleases have garnered considerable attention due to their capacity for single-nucleotide discrimination. Leveraging the A367G SNP within the MS obg gene, we developed a novel identification method that integrates PfAgo-mediated cleavage with PCR amplification. Through systematic optimization of PfAgo cleavage substrates and PCR primers, this approach achieved detection sensitivities of 1 × 10 3 copies/µL for the MS-H vaccine strain and 1 × 10 4 copies/µL for wild-type strains. Validation using 12 clinical samples resulted in the accurate identification of three MS-H vaccine strains and nine wild-type strains. The established method thus provides a reliable and sensitive tool for discriminating between MS-H vaccine and wild-type strains, supporting improved surveillance and control in poultry farming.